The Land Snails of Tennessee - Leslie Hubricht (Hello World!, 1973)
This paper list of land snails in Tennessee as represented by specimens in the collection of the author. Most of the records are from the eastern half of the state, with only scattered records from the western part. As in previous paper said the series, only the counties are listed for the records